Risk Factors for Multidrug Resistant organisms in Exacerbation of COPD - Shakil, Mohammad Shahjahan Siddike; Jahan, Rowshne; Anam, Dr Md Khairul; Nafisa, Tasnim; Karim, Mohammad Ezazul; Rahman, Md Mahabubur; Kabir, Muhammad Humayoun; Chatterjee, Amit (Chest & Heart Journal, 2023)
Background & Objective: Bacterial infections are the major cause of acute exacerbation of COPD (AE-COPD). The natural history of chronic obstructive pulmonary disease is characterized by frequent exacerbations. Majority of exacerbations are infectious and bacteria responsible for 30-50% of these cases. Appropriate use of antibiotic reduce mortality, hospital stay, subsequent exacerbations, further lung damage and also prevention of development of antibiotic resistance. Patients & Methods: This cross sectional observational and analytical study conducted at the Department of Respiratory Medicine in National Institute of Diseases of the Chest and Hospital from July 2019 – June 2020. A total of 102 patients with acute exacerbation of COPD were enrolled in this study. Early morning Sputum were examined for bacteriological culture and sensitivity. Multidrug-resistance was determined according to European Centre of Disease Prevention and Control classification. Result: One hundred and two exacerbations were included and microorganisms were isolated in 50 cases. Pseudomonas aeruginosa15(30%),Klebsiella pneumoniae14(28.0%) and Acinetobacter 11(22%) were more frequent. Multidrug-resistant pathogens were found in 35(70%) cases. In multivariateanalysis,preevious hospitalization (Odds ratio2.19,95% CI 1.22-3.91), frequent antibioticuse (OR 3.136, 95% CI 1.37-7.15) and chronic kidney disease (7.560,95%CI 1.82-31.33) were found to be independent predictors for MDR pathogens. Irregular use of antibiotics (p<0.007) among the frequent antibiotic users favored growth of MDR pathogen. Conclusion: Recent hospitalization, frequent antibiotic users particularly indiscriminate use of antibiotics and chronic kidney disease were seemed to be the risk factor for multidrug resistant bacteria.So special attention should be warranted in these groups regarding use of antibiotics. Chest Heart J. 2021; 45(1) : 40-46